Does patient-specific instrumentation in primary total knee arthroplasty improve long-term satisfaction or function? A randomized trial with a 9-year follow-up - Caldeira-Dantas, Sofia; Gonçalves, Marta; Vaz-Pinto, Gonçalo; Dias, Pedro; Marreiros, Ana; Fontes, Ana Paula; Sousa, João P. (International Journal of Research in Orthopaedics, 2024)
Background: Patient-specific instrumentation (PSI) aims to increase the accuracy of total knee arthroplasty (TKA). However, the long-term benefit compared to conventional instrumentation (CI), is still controversial. This randomized controlled trial compares the long-term outcomes between PSI and CI in TKA. Methods: Patients submitted to PSI or CI TKA with a minimum follow-up of 8 years were evaluated. Satisfaction levels, forgotten joint score (FJS) and Western Ontario and McMaster university osteoarthritis index (WOMAC) scores were compared. Regarding descriptive statistics, mean, standard deviation and frequencies were obtained. For inferential statistics we used the t test for independent samples the Mann-Whitney test and the Wilcoxon Test. Results: A total of 50 TKA were included (48% CI; 52% PSI) with an average follow-up time of 9.3 years. At the final follow-up the WOMAC score was similar between groups (p=0.846; CI:26.8±22.5; PSI:26.8±25.3). Similarly, no differences were seen for the FJS (p=0.785; CI:59.6±35.1; PSI:57.1±36.2) or satisfaction (p=0.486; CI:8.1±2.8; PSI:9.1±1.4). However, at the final follow-up, the total WOMAC score had worse results when compared to the previous evaluations (p=0.013 for CI group; p=0.009 for PSI group). No significant differences in the satisfaction levels were detected regarding the initial and final evaluations (p=0.581 for CI group; p=0.936 for PSI group). Conclusions: Nine years after TKA, PSI and CI patients reported similar levels of satisfaction and functioning. Both groups achieved similar results concerning the WOMAC, FJS scores and satisfaction levels. This study suggests that long-term satisfaction and functioning levels are similar in both PSI and CI.